MEDIA MANAGEMENT FOR DAKHAH IN THE DIGITAL ERA: A SYSTEMATIC REVIEW OF STRATEGY, INNOVATION, AND SUSTAINABILITY ROADMAP - Roa'zah, Nandipah; Sukirno, Sukirno; Nuruzzaman, Moh. Agil; Supeno, Supeno; Munahar, Munahar; Muazaroh, Muslimatun Diana; Afifah, Diana Elfiyatul; Ghozali, Moh Imam (Westscience Press, 2025)
Digital transformation has shifted the paradigm of da'wah from a traditional, linear approach to a participatory, network-based, and experience-oriented model. This article presents a narrative systematic review of the current literature (2020–2025) to analyze da'wah media management in the context of digital dynamics. The research findings reveal that the effectiveness of digital da'wah depends not only on technology adoption, but on the synergistic integration of three main pillars: (1) systematic management principles that combine data-driven planning with authentic Islamic values; (2) innovative content and platform strategies that are creative, interactive, and in line with the preferences of the younger generation (millennials and Gen Z); and (3) strengthening two-way interactions and digital branding to build sustainable online communities. This study also identifies the potential of immersive technologies (AR/VR) and the importance of media production competencies. As a synthesis, a three-layer integrative model (value-strategy foundation, content-technology execution, and relationship-branding) is proposed that can serve as a guide for academics and practitioners. Practical implications emphasize investing in team capacity, audience-centric content strategies, judicious exploration of technology, and a focus on relationship building. Thus, this article offers a conceptual and operational framework for optimizing digital da'wah media to remain relevant, effective, and transformative in the 21st century.